2015
DOI: 10.1128/aac.04433-14
|View full text |Cite
|
Sign up to set email alerts
|

Broad Coverage of Genetically Diverse Strains of Clostridium difficile by Actoxumab and Bezlotoxumab Predicted by In Vitro Neutralization and Epitope Modeling

Abstract: Clostridium difficile infections (CDIs) are the leading cause of hospital-acquired infectious diarrhea and primarily involve two exotoxins, TcdA and TcdB. Actoxumab and bezlotoxumab are human monoclonal antibodies that neutralize the cytotoxic/cytopathic effects of TcdA and TcdB, respectively. In a phase II clinical study, the actoxumab-bezlotoxumab combination reduced the rate of CDI recurrence in patients who were also treated with standard-of-care antibiotics. However, it is not known whether the antibody c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…Both antibodies fully neutralized the effects of their respective toxins from all ribotypes tested (Figure 7C and D). However, the neutralization potencies of both antibodies for toxins of ribotypes 027 and 078 were significantly lower than toxins of ribotype 087, similar to data obtained in the Rac1 glucosylation assay above (Section 2.3) and consistent with previous data in the SRB assay [15].…”
Section: Toxin-induced Cytotoxicity (Step 5 Insupporting
confidence: 81%
See 3 more Smart Citations
“…Both antibodies fully neutralized the effects of their respective toxins from all ribotypes tested (Figure 7C and D). However, the neutralization potencies of both antibodies for toxins of ribotypes 027 and 078 were significantly lower than toxins of ribotype 087, similar to data obtained in the Rac1 glucosylation assay above (Section 2.3) and consistent with previous data in the SRB assay [15].…”
Section: Toxin-induced Cytotoxicity (Step 5 Insupporting
confidence: 81%
“…Notably, the potency of actoxumab and bezlotoxumab on their respective toxins was lower for toxins of ribotype 027 and 078 compared to ribotype 087. This is consistent with the lower affinities of the antibodies against toxins of these ribotypes, as previously described by Hernandez et al [15]. Figure 1)…”
Section: Clostridium Difficile -A Comprehensive Overviewsupporting
confidence: 79%
See 2 more Smart Citations
“…Based on this assessment, we can reasonably conclude that bezlotoxumab should interact with target epitopes both in TcdB 027 and TcdB 012 , yet the neutralization experiments suggest that TcdB 027 is less sensitive to the antibody (30). More recently, Hernandez et al (33) performed a comprehensive analysis of bezlotoxumab reactivity with TcdB from several ribotypes and found that subtle sequence variations do indeed affect the EC 50 , but this can be overcome by reasonable increases in the amounts of antibody applied to the toxin. The extent to which intramolecular or intermolecular interactions shield these and other specific neutralizing epitopes has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%